Study on effect of slit rotor poles to the switched reluctance motor performance / Nik Muhammad Fahim Nik Mohammad Dziauddin - Nik Mohammad Dziauddin, Nik Muhammad Fahim (2014)
Switched Reluctance motor is a type of reluctance motor in which the operation is depending on the reluctance torque produced. SRM is popular for modern motors as it only uses switching system and does not have to be an input power to power up the motor. The main purpose of this project is to improve the efficiency of the SRM. The slitting technique will be used on the rotor pole to create a small fringe to each of the rotor pole and this will be done in FEMM and the model of SRM will be designed in FEMM too. A script file will be used to animate the stepping function for the SRM and allow to see the flux distribution. The current and inductance value can be obtained from the results of the simulation. The motor model used is a 6/6 poles switched reluctance motor which all phases will be turn on at once. The optimum output can be produced by having modification to the rotor poles of maximum five slit.